2013
DOI: 10.1002/jemt.22290
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial ultramorphology evaluation of resin luting cements to dentin: A correlative scanning electron microscopy and transmission electron microscopy analysis

Abstract: The objective of this study was to analyze the dentin-resin cements interfacial ultramorphologies using two different methods: scanning (SEM) and transmission electron microscopy (TEM). Four commercial products were evaluated: two conventional cementing system (RelyX ARC/Adper™ Scotchbond™ Multi-Purpose Plus, 3M ESPE and Clearfil Esthetic Cement/DC Bond, Kuraray) and two self-adhesive resin cements (RelyX Unicem, 3M ESPE and Clearfil SA Cement, Kuraray). Prepolymerized resin disks (Sinfony, 3M ESPE) were cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Due to the use of a bonding system, the luting procedure with conventional resin cements form the interlocking structure known as hybrid layer, presenting good bonding and longevity (4). However, in spite of being extensively used nowadays, the self-adhesive resin cements are still progressing and only one brand has been studied more extensively (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the use of a bonding system, the luting procedure with conventional resin cements form the interlocking structure known as hybrid layer, presenting good bonding and longevity (4). However, in spite of being extensively used nowadays, the self-adhesive resin cements are still progressing and only one brand has been studied more extensively (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of being extensively used nowadays, the self-adhesive resin cements are still progressing and only one brand has been studied more extensively (1). Furthermore, no hybridization was detected for the self-adhesive resin cements (4) and the bond strength was lower compared to the conventional resin cements (5,6). Thus, more studies would bring important information regarding its bond capability to dental substrate, especially in some issues such as bond strength to dentin after the application of different instruments to finish the tooth preparation.…”
Section: Introductionmentioning
confidence: 99%
“…While morphological imaging techniques have demonstrated a thin hybrid layer for self-etch cements, no such formation was observed for self-adhesive cements, despite the intimate adaptation between the cement and the dental substrate. [13][14][15][16][17][18][19] De Munck et al, 19 with the use of TEM analysis, observed an irregular interaction zone at the interface between dentin and a self-adhesive cement, ranging from 0 up to 2 μm.…”
Section: Figmentioning
confidence: 99%
“…12 However, several studies based on different morphological imaging methods have been unable to demonstrate evidence of dentin decalcification achieved by the self-adhesive resin cements investigated and their infiltration into dentin. [13][14][15][16] Although studies have observed an intimate adaptation of self-adhesive resin cements to dentin, no hybrid layer or resin tag formation could be identified. [17][18][19] An established hybridization is typically observed with the use of total-etch or self-etch cements, whereas more superficial physical interactions and possible involvement of chemical reactions between the material and dental hard tissues have been found with self-adhesive cements.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested dental substrate treatment that can enhance both the hybrid layer and bond strength results. Furthermore, it is not yet clear whether enamel conditioning with phosphoric acid is clinically required before luting with self-adhesive cements 3,[6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%